Record of damage by Aulacoscelis melanocera (Coleoptera: Orsodacnidae) on Cycas revoluta (Cycadaceae) in Campeche, Mexico - Sánchez-Soto, Saúl (Revista Colombiana de Entomología, 2020)
On May 7, 2018, in the garden of an archaeological site in northern Campeche, Mexico, a Cycas revoluta plant was observed with approximately 40 % of the foliage damaged by a swarm of Aulacoscelis melanocera (Coleoptera: Orsodacnidae). The present work constitutes the first report of this species causing severe damage in C. revoluta and the first record of this insect for the state of Campeche.